Layer Selective Control of the Lattice Structure in Oxide Superlattices. (24th October 2013) - Frano, Alex; Benckiser, Eva; Lu, Yi; Wu, Meng; Castro‐Colin, Miguel; Reehuis, Manfred; Boris, Alexander V.; Detemple, Eric; Sigle, Wilfried; van Aken, Peter; Cristiani, Georg; Logvenov, Gennady; et al.
<x xml:space="preserve">Abstract</x> A combined synchrotron X‐ray diffraction and transmission electron microscopy study reveals a structural phase transition controlled by the overall thickness of epitaxial nickelate‐aluminate superlattices. The transition between uniform and twin‐domain states is confined to the nickelate layers and leaves the aluminate layers unaffected. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>